2016
DOI: 10.21566/tarbitderg.280319
|View full text |Cite
|
Sign up to set email alerts
|

Bazı Arpa Genotiplerinin Diyarbakır ve Şanlıurfa Koşullarında Verim ve Kalite Özellikleri Açısından İncelenmesi

Abstract: ÖzBu çalışmada, Dicle Üniversitesi Ziraat Fakültesi tarafından geliştirilen arpa genotiplerinin standart çeşitler karşısında verim ve kalite özellikleri bakımından farklılıklarının araştırılması amaçlanmıştır. Araştırma, tesadüf blokları deneme desenine göre, [2013][2014] Investigation of Yield and Quality Parameters of Barley Genotypes in Diyarbakır and Şanlıurfa Conditions AbstractThe aim of this study was to investigate the differences of barley genotypes that developed by Dicle University agricultural fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…As compatible with this study, some other studies were reported that the negative relationship between GY and DTH is meaningful (Öztürk et al, 2014; Öztürk et al, 2016). Again, it was reported by some researchers that there was a negative correlation between GY and PC, in compatible with this study (Kızılgeçi et al, 2016;Kızılgeçi et al, 2019). While the negative correlation of PGR with DTH and LS was found to be significant (p <0.05), the relationship, with TGW was found to be positively significant (p <0.01).…”
Section: Correlations Between Traits (Gy)supporting
confidence: 91%
“…As compatible with this study, some other studies were reported that the negative relationship between GY and DTH is meaningful (Öztürk et al, 2014; Öztürk et al, 2016). Again, it was reported by some researchers that there was a negative correlation between GY and PC, in compatible with this study (Kızılgeçi et al, 2016;Kızılgeçi et al, 2019). While the negative correlation of PGR with DTH and LS was found to be significant (p <0.05), the relationship, with TGW was found to be positively significant (p <0.01).…”
Section: Correlations Between Traits (Gy)supporting
confidence: 91%
“…The highest number of SPSM was observed in genotype G21 in irrigated trials and G9 in rainfed conditions. Researchers have previously reported that the number of SPSM varies according to sowing norms, variety, sowing time, available water, and climate and soil conditions (Kılıç et al, 2010;Kızılgeçi et al, 2016). Although heredity also has a significant role in determining SPSM, this parameter is also influenced by resistance of genotypes to adverse environmental conditions, such as temperature, drought stress, and frost.…”
Section: Spikes Per Square Meter (Spsm) (Number)mentioning
confidence: 99%
“…In contrast, TKW decreased with increasing N application, probably because increasing the N application rate increased the number of seeds per spike, thereby minimizing the TKW (Kızılgeçi et al., 2016; Needham & Boyd, 1976). Hadi et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, all traits demonstrated a positive direct effect at the high N application level with ANUE, except GFD and HD, which demonstrated a negative direct effect. However, at low N, only TKW showed a negative direct effect with ANUE (Kızılgeçi et al., 2016; Weston et al., 1993). Overall, based on the path analysis results, the selection of NUE using the direct effect was the best method for evaluating NE.…”
Section: Discussionmentioning
confidence: 99%